(7x+9)+(4x+9)+(8x-36)+109+(5x-7)=540

Simple and best practice solution for (7x+9)+(4x+9)+(8x-36)+109+(5x-7)=540 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x+9)+(4x+9)+(8x-36)+109+(5x-7)=540 equation:



(7x+9)+(4x+9)+(8x-36)+109+(5x-7)=540
We move all terms to the left:
(7x+9)+(4x+9)+(8x-36)+109+(5x-7)-(540)=0
We add all the numbers together, and all the variables
(7x+9)+(4x+9)+(8x-36)+(5x-7)-431=0
We get rid of parentheses
7x+4x+8x+5x+9+9-36-7-431=0
We add all the numbers together, and all the variables
24x-456=0
We move all terms containing x to the left, all other terms to the right
24x=456
x=456/24
x=19

See similar equations:

| 8x24+14=8x+5 | | 3/2x+1=5/4x-5 | | 22+53x=-20+60x | | 6a=8.4 | | f=1.5-9 | | 4/x+4-2/4x+16=15 | | -22+36v=-22(1+2)2v | | -22+36v=-22(1+22v | | 7^-x=4.6 | | 3/2x+1=5/4+5 | | 18(x+12)=396 | | 0.6(10x+15)=3.5(0.2+5) | | a−1/5=−1/7 | | 7x+8/2+4x-1/6=33 | | –8v+6=–10v | | `11+3x-7=6x+5-3x | | 3m+–7=–13 | | 4x-8/3+9x+6/2=12 | | 3x(x)=46 | | 9d+4d-2d+8=-3d | | 3(x+3)=2x-87x | | -5x+4=-5x+16 | | 3(x+1)-5=3x=-2 | | -3x+7(x-8)=-8 | | 7x/2-2=26 | | 9/5x=8 | | 4x+4/5=11/5 | | (9j+7)(8j+5)=0 | | 5x-2(2x-7)=(3x-1)+7/2 | | 4x4/5=11/5 | | 15=23x;x= | | 15x+150=480 |

Equations solver categories